64Cu-based Radiopharmaceuticals in Molecular Imaging. (19th July 2019) - Zhou, Yeye; Li, Jihui; Xu, Xin; Zhao, Man; Zhang, Bin; Deng, Shengming; Wu, Yiwei
Copper-64 (T1/2 = 12.7 hours; β + : 19%, β − : 38%) has a unique decay profile and can be used for positron emission tomography imaging and radionuclide therapy. The well-established coordination chemistry of copper allows for its reaction with different types of chelator systems. It can be linked to antibodies, proteins, peptides, and other biologically relevant small molecules. Two potential ways to produce copper-64 radioisotopes concern the use of the cyclotron or the reactor. This review summarized several commonly used biomarkers of copper-64 radionuclide.